Pengembangan Aplikasi Kuis Interaktif Untuk Membantu Proses Evaluasi Hasil Belajar Peserta Didik SMK Negeri 2 Yogyakarta Berbasis Android - Rifaldi Iqbal Bachtiar; Nurkhamid (Journal of Information Technology and Education (JITED), 2023)
The purpose of this research are: (1) Developing an android-based quiz application as a media evaluation assessment in learning implementation activities, (2) Testing application quality standards according to ISO 25010 with the characteristics of functional suitability, usability, compatibility, and performance efficiency. The method used is Research and Development (R&D) with the Rational Unified Process (RUP) application development procedure which consists of 4 phases, inception, elaboration, construction, and transition The results of this research are (1) Android application "QuizQuy" was developed with RUP model, and (2) application has met the ISO 25010 testing standard in aspects of (a) functional suitability features can run 100%, (b) usability with score 91.73%, (c) compatibility 100% in terms of coexistence, and various operating systems also devices, (d) performance efficiency gets a good score with an average CPU usage of 22.5% , memory usage of 203.65 MB and time behaviour of 0.02 seconds/thread without any force close or memory leak in the application.